Klotho, Oxidative Stress, and Mitochondrial Damage in Kidney Disease - Javier Donate-Correa; Beatriz Martín-Carro; Jorge B. Cannata-Andía; Carmen Mora-Fernández; Juan F. Navarro-González (MDPI AG, 2023)
Reducing oxidative stress stands at the center of a prevention and control strategy for mitigating cellular senescence and aging. Kidney disease is characterized by a premature aging syndrome, and to find a modulator targeting against oxidative stress, mitochondrial dysfunction, and cellular senescence in kidney cells could be of great significance to prevent and control the progression of this disease. This review focuses on the pathogenic mechanisms related to the appearance of oxidative stress damage and mitochondrial dysfunction in kidney disease. In this scenario, the anti-aging Klotho protein plays a crucial role by modulating signaling pathways involving the manganese-containing superoxide dismutase (Mn-SOD) and the transcription factors FoxO and Nrf2, known antioxidant systems, and other known mitochondrial function regulators, such as mitochondrial uncoupling protein 1 (UCP1), B-cell lymphoma-2 (BCL-2), Wnt/β-catenin, peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 alpha), transcription factor EB, (TFEB), and peroxisome proliferator-activated receptor gamma (PPAR-gamma). Therefore, Klotho is postulated as a very promising new target for future therapeutic strategies against oxidative stress, mitochondria abnormalities, and cellular senescence in kidney disease patients.